Bifidobacterium species serve as key gut microbiome regulators after intervention in gestational diabetes mellitus - Cui, Zifeng; Wang, Shuxian; Niu, Jianhua; Ma, Jingmei; Yang, Huixia (BMC microbiology, 2024)
Gut microbiome dysbiosis is associated with gestational diabetes mellitus (GDM), and its modulation represents a promising approach for enhancing glycemic control. In this study, we aimed to discover specific alterations in the gut microbiome through lifestyle management. We performed metagenome sequencing on fecal samples and measured short-chain fatty acid (SCFA) in plasma samples from 27 well-controlled GDM pregnancies before and after glycemic control. At the same time, 38 normal glucose tolerance (NGT) samples served as controls. Additionally, we employed two-sample Mendelian Randomization (MR) to validate our findings against Genome-Wide Association Study (GWAS) database. Our dynamic analysis revealed Bifidobacterium genus increased in GDM patients after intervention. The MR analysis confirmed that the family of Bifidobacteriaceae (OR 0.929, 95% CI, 0.886-0.975; P = 0.003) was the only negatively associated family with GDM. Further analysis indicated the increased abundance of Bifidobacterium species were negatively correlated with glycemic traits (Spearman rho mean - 0.32 ± 0.34) but positively correlated with plasma SCFA levels (Spearman rho mean 0.24 ± 0.19). Functional analysis revealed that the quorum-sensing pathway had the strongest effect on the ability of Bifidobacterium to promote glucose homeostasis (Spearman rho = -0.34), suggesting its role in regulating intestinal microbiota. Finally, the multivariable MR analysis demonstrated that two pathways, COLANSYN PWY and PWY 7323, responsible for cell surface compound synthesis in gram-negative bacteria, mediated 14.83% (P = 0.017) and 16.64% (P = 0.049) of the protective effects of Bifidobacteriaceae against GDM, respectively. In summary, Bifidobacterium is an effective gut microbiota regulator for GDM-related glucose homeostasis.